101 clinical cases in emergency room - Zaheer, Badar M. (Jaypee Brothers Medical Publishers, 2014)
Quick reference guide to emergency medicine for clinicians and trainees. Presented as clinical case studies, it is divided over 21 chapters, each covering scenarios in different body systems. Cases are presented in an easy to read format, helping trainees form a diagnosis and quick treatment plan. The final section covers disaster management.